Offspring behavior is affected by fructuose-induced insulin resistance in wistar rat dams - Gutierrez, Bárbara Judith (2020)
Maternal nutrition before and during pregnancy plays a critical role in fetal brain development. Epidemiological studies have shown an association between maternal obesity and adverse neurodevelop- mental outcomes for offspring. The effects of pregestational insu- lin resistance (PIR) on intrauterine programing of fetal brain is a lesser-explored area. The goal of this study was to investigate the impact that PIR has on neurodevelopmental reflexes and behavior during adulthood. Offspring behavior was evaluated using open field (OF), marble burying, tail flick and elevated plus maze (EPM) tests. Wistar adult rats received fructose enriched water (10 % or 20% w/v) before pregnancy to induce PIR, and during gestation. No modifications on the developmental milestones nor neonates size were observed when comparing offspring of control and PIR dams. Smelling, rearing and climbing frequency as well as duration during exploratory behavior testing in the OF test decreased in PIR dams progeny. Analysis of minute-by-minute duration in the EPM assay evidenced that the PIR group spent more time in the central square and less in the closed arms compared to control group. Fur- thermore, offspring of PIR dams showed a more frequent stretch-at- tend posture in the central square. Offspring exposed to maternal fructose intake had a greater latency of tail withdraw in the tail flick test and buried more marbles in the marble test. We conclude that maternal exposure before and during gestation to fructose does not affect primitive reflexes such as body righting mechanisms, coordination, strength, sensory system maturation, and labyrinthine reflex. On the contrary, adult rat behavior was sig- nificantly altered. Particularly, our results evidence an increment on anti-anxiety like behavior; longer decision-making time and risk assessment. Obsessive-compulsive disorder behavior and altered nociception were also noted.